Handbook of biomechatronics - Segil, Jacob (London : Academic Press, is an imprint of Elsevier, 2019)
Handbook of Biomechatronics provides an introduction to biomechatronic design and an in-depth explanation of some of the most exciting and groundbreaking biomechatronic devices in the world. Edited by Dr. Jacob Segil and written by a strong team of biomechatronics experts, the book covers biomechatronic design, components, and specific biomechatronic devices that span many disciplines. Sections cover sensors, actuators, processing and control systems, and signal processing. In addition, a chapter on biomechatronic devices contains distinct examples, spanning hearing aids to brain-machine interfaces. Each chapter presents the development phase of a biomechatronic device that is followed by an in-depth discussion of the current state-of-the-art.
Includes bibliographical references and index.
Keywords: Mechatronics -- Handbooks, manuals, etc; Biological systems -- Handbooks, manuals, etc